Errors Analysis towards Collocation Usage - Taufiq Kurniawan; Abdurrahim Abdurrahim (Universitas 45 Surabaya, 2023)
The purpose of this research was to analyse the use of collocation in Speaking Skill for students of English language department of Hamzanwadi University. This research employed descriptive qualitative research design. The participants of this study comprised ten students from the fourth semester of English Department. The data was collected by three research instruments which were observation, questionnaire, and interview. The interview result showed that the understanding and students’ ability were still low frequency in using collocation and just a few of them had average frequency in the use of collocation. Moreover, the questionnaire result showed that there was only one student who had seven scores, three students had six scores, four students had five scores, and two students had three scores. It proved that they still had low frequency in using collocation in speaking. Based on this result, it is important to teach and learn the use of collocation in terms of speaking both verbally and contextually. Apart from increasing vocabulary and speaking skills, it will also facilitate other English skills such as writing and reading in academic context.